The crystal structure and cytotoxicity of Centrosymmetric Copper(II) complex derived from S-methyldithiocarbazate with isatin - Abdul Manan, Mohd Abdul Fatah; Mohamed Tahir, Mohamed Ibrahim; Crouse, Karen Anne; Rosli, Rozita; How, Fiona Ni Foong; Watkins, David J. (Springer New York LLC, 2011)
Copper(II) complex of S-methyldithiocarbazate with isatin has been prepared and screened for their cytotoxic activities against MCF-7 (Human non-metastatic mammary gland adenocarcinoma cell line) and MDA-MB- 231 (Human metastatic mammary gland adenocarcinoma cell line). The compound crystallized in an orthorhombic crystal system with a space group C 2cb and was found to be selectively active against MCF-7 cell line (Human nonmetastatic mammary gland adenocarcinoma cell line with an IC50 value 0.45 lg/mL. The crystal structure of this centrosymmetric Cu(SMISA)2 complex (SMISA = Schiff base formed by condensation reaction of S-methyldithiocarbazate with isatin) showed that the copper atom has a distorted square-planar geometry with the Schiff base coordinated to the metal ion as a uninegatively charged bidentate ligand through the azomethine nitrogen and thiolate sulfur.